Bacteria as food in aquaculture: do they make a difference?. (7th June 2016) - Nevejan, Nancy; De Schryver, Peter; Wille, Mathieu; Dierckens, Kristof; Baruah, Kartik; Van Stappen, Gilbert
Abstract: Bacterioplankton is an important component of marine as well as fresh waters and accounts for a large fraction of the production of particulate matter in those ecosystems. The concept of bacteria as providers of essential nutrients in aquatic food webs has been raised most recently in relation to the utilization of bacteria as a food source in aquaculture food chains. This article represents a comprehensive review on the potential role of bacteria as a direct food source for aquaculture organisms. After studying shortly the analytical tools that can be applied to determine the uptake and assimilation of bacteria by higher trophic levels, it describes the bacterial loads that are found in closed and open aquaculture systems and elaborates on the composition of bacteria from a nutritional point of view. Next this study elaborates in more detail on the role of bacteria as food for the zooplankton groups used as live food in aquaculture hatcheries and for various groups of aquaculture target organisms, such as fish, crustaceans and especially bivalves. This includes an assessment of the specific uptake mechanisms of the different taxonomic groups of interest in relation to their efficiency to ingest bacteria. Finally, future research lines are suggested to elucidate the nutritional impact of the bacterial community in aquaculture systems and how to steer this in order to optimize the production.